The Effect of Giving Educational Animated Videos and Booklets on Parents’ Knowledge About Stimulation of Language with Preschool Children - Nurjanah, Desi Tribuana; Indarwati, Ferika; Rahmah, Rahmah; Suminar, Istinengtiyas Tirta (Jurnal Keperawatan Profesional, 2025)
Language development is an important aspect of the golden period of child development, yet limited parental knowledge and inadequate stimulation may hinder optimal progress. This study aims to assess the effectiveness of education using animated videos and booklets in improving parents’ knowledge of language development stimulation in preschool-aged children. The study employed a quasi-experimental design with pre-test and post-test. The sample consisted of 120 parents divided into an intervention group (n=60) and a control group (n=60). The intervention group received a 10-minute animated video and a booklet, while the control group received a leaflet. All materials were delivered once via WhatsApp and studied independently with unrestricted access for review. The instrument used was a 15-item questionnaire that had been tested for validity and reliability. Data were analyzed using paired t-tests and independent t-tests. The results showed a significant increase in knowledge in both groups, with a greater improvement in the intervention group (7.63 to 12.10) compared to the control group (7.52 to 8.90). Independent t-test analysis indicated a significant difference between groups (p = 0.001). The study concludes that animated videos and booklets are more effective than leaflets in enhancing parental knowledge. These findings support the utilization of accessible digital media as a sustainable strategy in educational programs at posyandu, early childhood education centers, and parenting trainings.